ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫНДА ШАРЎАШЫЛЫҚТЫ РАЎАЖЛАНДЫРЫЎ ҲӘМ ӨНИМ САПАСЫН ЖАҚСЫЛАЎ - Наўрызов, Т.Қ. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of the development of stock-breeding branch and increasing the quality of product in farming and private subsidiary husbandries. The author also studies the hays of organizing the care and feeding, dealing with tribal work in cattle breeding in these husbudries.
Keywords: dips; the region; agro area; silos; haylage; roughage